TINGKAT PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN KAWASAN AGROPOLITAN PAYANGAN, BALI - Ni Made Dwi Kurnia Ashari; Komang Wirawan; I Nyoman Harry Juliarthana (UNHI PRESS, 2022)
The agropolitan program is an area development program that seeks to reduce the gap between cities and villages. This program is implemented through human resource development programs and improvement of infrastructure facilities. The purpose of this study is to analyze the level of participation and form of society as well as the factors that influence community participation in agropolitan programs.This study used a descriptive research method with a qualitative approach and supported by quantitative data obtained through interviews and questionnaires to randomly selected respondents. Data will be analyzed using descriptive statistical analysis method.Based on the data analysis carried out, it was concluded that the level of community participation in Kerta Village indicated that the level of community participation was at the non-participation level in all stages of the program with the form of participation dominating in the form of labor.